2010
DOI: 10.1210/er.2009-0046
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Action in Hyperthyroidism: A Focus on Muscle and Adipose Tissue

Abstract: Hyperthyroidism leads to an enhanced demand for glucose, which is primarily provided by increased rates of hepatic glucose production due to increased gluconeogenesis (in the fasting state) and increased Cori cycle activity (in the late postprandial and fasting state). Adipose tissue lipolysis is increased in the fasting state, resulting in increased production of glycerol and nonesterified fatty acids. Under these conditions, increased glycerol generated by lipolysis and increased amino acids generated by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 163 publications
1
88
0
5
Order By: Relevance
“…Thyroid hormones regulate the metabolism of the whole human body -triiodothyronine (T3) is necessary to maintain the energy requirements of various cells and tissues, to balance their anabolism and catabolism, and regulate body weight [1][2][3][4]. An abnormal amount of T3 disturbs a number of metabolic processes [2]: shortage of T3 in hypothyroidism reduces basic metabolic rate and thermogenesis, inhibits catabolism and gains total body weight [5]; excess of T3 in hyperthyroidism reverses these processes [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormones regulate the metabolism of the whole human body -triiodothyronine (T3) is necessary to maintain the energy requirements of various cells and tissues, to balance their anabolism and catabolism, and regulate body weight [1][2][3][4]. An abnormal amount of T3 disturbs a number of metabolic processes [2]: shortage of T3 in hypothyroidism reduces basic metabolic rate and thermogenesis, inhibits catabolism and gains total body weight [5]; excess of T3 in hyperthyroidism reverses these processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…An abnormal amount of T3 disturbs a number of metabolic processes [2]: shortage of T3 in hypothyroidism reduces basic metabolic rate and thermogenesis, inhibits catabolism and gains total body weight [5]; excess of T3 in hyperthyroidism reverses these processes [6]. Specific therapy of hypo- [7,8] and hyperthyroidism [9][10][11] restores proper body mass.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that TH levels affect not only glycaemic control but also hepatic and muscular insulin resistance and play a major role in energy homeostasis [1]. Both hypothyroidism and thyrotoxicosis have been shown to increase insulin resistance [2]. Decompensated hyperthyroidism can worsen glycaemic control and predispose patients to diabetic ketoacidosis [3].…”
mentioning
confidence: 99%
“…In the present study we observed a several fold increase in the fasting serum insulin levels in the overt and subclinical-hyperthyroid patients. This controversy in the circulating insulin concentration may be attributed to the varying rates of insulin catabolism in these patients [19]. It has been reported that exposure of immature pancreatic islets of the rat to thyroid hormones enhanced their maturation and secretion of the glucose-responsive insulin [20], and induced the expression of thyroid hormone-receptors and deiodinase enzymes [21].…”
Section: Discussionmentioning
confidence: 99%